Establishment and application of a triplex real-time PCR assay for detection of porcine circoviruses - Cheng, Ze; Wang, Zenglin; Quan, Lizhu; Zhang, Zhendong; Wang, Wenqiang; Wen, Wei; Zhu, Zhenbang; Li, Xiangdong (Frontiers in Veterinary Science, 2025)
Porcine circovirus disease represents a prevalent ailment that is principally manifested by a series of clinical symptoms, including reproductive disorders in sows and high mortality rates in piglets. It has brought huge economic losses upon the global swine industry. Furthermore, the symptoms triggered by different genotypes of porcine circovirus bear resemblance and difficult to distinguish. Therefore, it is essential to establish a rapid, accurate, time-efficient, and high-throughput triplex real-time PCR differential diagnosis assay for detecting PCV2, PCV3, and PCV4. In this study, specific primers and probes were designed based on the conserved sequences of ORF1 sequences of PCV2, PCV3, and PCV4. The triplex Real-Time PCR assay was established and optimized, which showed satisfactory specificity, sensitivity, repeatability, and reproducibility. The limit of detection (LOD) was determined to 4.8×101 copies/μL. The correlation coefficients R2 exceeded 0.999, and no cross-infection was found with other porcine viral pathogens. In addition, both the intra-repeatability and inter-repeatability were lower than 2%, which further attests to the reliability and stability of this assay. The complete consistency of the detection results with those of the commercial single-plex real-time PCR kits indicates that the established assay has satisfactory accuracy. The established assay was next applied to detect 370 clinical samples that were collected from 2023 to 2024 in the northern Anhui province of China. The results showed that the positive rate of PCV2 was 81.35% (301/370), the positive rate of PCV3 was 72.43% (268/370), and the positive rate of co-infection of PCV2 and PCV3 was 38.37% (142/370). However, PCV4 was not detected. Therefore, the established triplex real-time PCR assay in this study provides a valuable tool for the detection of porcine circovirus, which facilitates the epidemiological investigation of porcine circovirus in China.